Human Rights and Pancasila: A Case of Tionghoa Ethnic Discrimination in Indonesia - Musa, Muhammad Rafhael Purnawan; Lesmana, Asep Berlian; Arthamevia, Restha Nourmalifa; Pratama, Prisna Adi; Savitri, Niken (Indonesian Journal of Pancasila and Global Constitutionalism, 2022)
Pancasila and Human Rights are a concrete form of implementing the constitution and protecting citizens in accordance with the goals of the nation as stated in the Preamble to the 4th paragraph of the 1945 Constitution of the Republic of Indonesia. In its implementation, Pancasila and Human Rights guarantee equality of all levels and groups of society in service and participation as citizens. The process of entering Chinese ethnicity into the civilization of Indonesian society certainly cannot be separated from various aspects, including history. Ethnic Chinese migrated to Indonesia through trade routes and gave birth to cultural acculturation. Over time, the influence of the presence of ethnic Chinese in Indonesia experienced upheavals, resulting in various discriminatory practices against them. The existence of discriminatory practices that occur shows that between the indigenous people and the Chinese there are gaps and various problems. Examples of discriminatory cases or practices that occurred include Riots during the reform era, restrictions on participation and political rights, expulsions, rapes, and others that are still happening today. In this case, the indigenous people feel competitive economically and in other aspects.